Zinc Oxide Eugenol-Formocresol Root Canal Treatment Fails to Treat a Deciduous Tooth with Dentoalveolar Abcess - Pediarahma, Arifa; Rizal, Mochamad F. (Journal of Dentistry Indonesia, 2014)
Irreversible pulp infection can lead to dentoalveolar abscess. Root canal treatment in deciduous teeth is indicated in irreversible pulp infection to maintain children’s health and deciduous teeth until its exfoliation period. Success rate of endodontic treatment in deciduous teeth can be enhanced by using antimicrobial root canal filling material. Combination of ZOE-formocresol as root canal filling material has a superior antimicrobial property. Unfortunately, based on some research it is also toxic to the tissue. This case report will discuss about failure of root canal treatment in deciduous tooth with dentoalveolar abscess using combination of ZOE-formocresol as obturating material. There are some factors that possibly cause the failure: complexity of deciduous molar anatomy, the choice of root canal filling material, application of root canal filling material that is not adequate, or an extend pathological condition.